The essence of passionarity as properties of personality - Ivanova, Yanna (Psyhology & society, 2019)
This article is devoted to clarification of psychological essence of passionarity as personal property. In the historical context the passionarity is considered as a process and property that sets the vector of development of society and personality. In the result of analysis and synthesis of ideas of different psychological schools was formulated author’s understanding of the passionarity. Outlined that psychological nature of passionarity is connected with existential aspects of human being, cognitive fixation on the purpose, with realization of personalized activity. Passionarity is substantiated as stable property of the personality (scilicet as a certain personal disposition) as its penchant for transformation, changing environment, aimed at implementing the functionally stable purpose in the subjective space of affirmation their own existence.